2011
DOI: 10.2495/sdp110421
|View full text |Cite
|
Sign up to set email alerts
|

The development of seaweed farming as a sustainable coastal management method in Indonesia: an opportunities and constraints assessment

Abstract: Indonesian coastal areas are continually experiencing pressures that affect their sustainability. Beginning in the 1980s, the Indonesian government has introduced numerous development programs to address this problem. One type of program is seaweed farming projects. The aim of these projects is to provide the fishing community with alternative, environmentally-friendly fishing activities, as well as improving its livelihood. The objective of this paper is to assess the opportunities and constraints of seaweed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…The average age found in this study was nearly the same as that in a previous study done by [20] in the Spermonde Islands, Indonesia. The percentage of farmers older than 55 was10.93 per cent.…”
Section: Respondent Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…The average age found in this study was nearly the same as that in a previous study done by [20] in the Spermonde Islands, Indonesia. The percentage of farmers older than 55 was10.93 per cent.…”
Section: Respondent Characteristicssupporting
confidence: 89%
“…Seaweed farming and fishing appear as a viable option for livelihood on average in the age group of 40 years in Lemo villlage. This result was similar to that found in the Spermonde Archipelago, Indonesia [20] and in North Sulawesi, Indonesia [18] where the farmers mostly have a primary level of education. In addition, the low level of education among farmers needs to be solved by specific training efforts to enable them to better take up their farming activities [18].…”
Section: Respondent Characteristicssupporting
confidence: 88%
“…According to Msuya (2011) and Zamroni and Yamao (2011), some men on Unguja started participating in seaweed farming as an alternative livelihood activity after failing in their main livelihood activities like fishing. Contrary to the men from Pemba Island, Zanzibar Island has fewer alternative income generating activities.…”
Section: Discussionmentioning
confidence: 99%
“…Conservationists and representatives of the seaweed industry have promoted seaweed mariculture as a sustain-able alternative livelihood to overfishing or destructive fishing practices (Sievanen et al 2005;Zamroni et al 2011;Robinson & Cruz 2015), although seaweed farming alone has not been found to reduce fishing pressure (Sievanen et al 2005) and has positive and negative impacts on farmers themselves (Supporting Information). Seaweed mariculture is also considered more environmentally benign than aquaculture of fish or crustaceans because cultivated seaweed neither requires feed nor produces organic or inorganic waste (Bryceson 2002;Rönnbäck et al 2002).…”
Section: Seaweed Cultivation As An Alternative Livelihoodmentioning
confidence: 99%